2019
DOI: 10.1002/col.22421
|View full text |Cite
|
Sign up to set email alerts
|

Improving unsupervised saliency detection by migrating from RGB to multispectral images

Abstract: Saliency detection has been an important topic during the last decade. The main goal of saliency detection models is to detect the most relevant objects in a given scene. Most of these models use RGB (Red, Green, Blue) images as an input because they mainly focus on applications where features (eg, faces, textures, colors, or human silhouettes) are extracted from color images, and there are many labeled databases available for RGB‐based saliency data. Nevertheless, the use of RGB inputs clearly limits the amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…We also performed a comparative analysis of the heat maps obtained with the RARE model for the RGB image and the different spectral bands. Our previous study [ 26 ] showed that using the information contained in the multispectral images and adapting the saliency models, there was an improvement in the model performance. The new analysis presented in this study used only individual bands and showed that each band was not enough to adequately predict the saliency maps obtained with the RGB image.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also performed a comparative analysis of the heat maps obtained with the RARE model for the RGB image and the different spectral bands. Our previous study [ 26 ] showed that using the information contained in the multispectral images and adapting the saliency models, there was an improvement in the model performance. The new analysis presented in this study used only individual bands and showed that each band was not enough to adequately predict the saliency maps obtained with the RGB image.…”
Section: Discussionmentioning
confidence: 99%
“…All the metrics were computed using one of the compared heat maps as ground truth and the other as test heat map. The heat map comparison metrics studied [ 26 ] are the following: Area under the curve (AUC): three different versions of this metric were computed: AUC-Borji (AUCB) [ 16 ], AUC-Judd (AUCJ) [ 14 ], and shuffled AUC (sAUC) [ 16 ]. For different values of threshold in the heat map, true positives and false positives are computed by using the other heat map.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Light consists of three primary colors popularly known as RGB, that is, Red-Green-Blue. 33,34 Computer screens can display images having a combination of these three colors band. When we combine these color bands, the result is a colored image having three primary color and their combination.…”
Section: Overview Of Nasa Landsat Programmentioning
confidence: 99%
“…If we consider only a single band of the image, it will appear like a grayscale image. Light consists of three primary colors popularly known as RGB, that is, Red‐Green‐Blue 33,34 . Computer screens can display images having a combination of these three colors band.…”
Section: Overview Of Nasa Landsat Programmentioning
confidence: 99%